Politik Hukum Pembentukan Komisi Yudisial - Abdul Khalik (SIMPUL: Jurnal Ilmu Politik dan Hukum, 2026)
The establishment of the Judicial Commission is part of the legal policy of reform aimed at strengthening the independence of the judiciary and enhancing the integrity of the judicial system in Indonesia. This article examines the legal policy behind the establishment of the Judicial Commission, its authority as stipulated by law, and its relevance from the perspective of maslahah. This study employs a normative legal method using a legislative and conceptual approach. The results of the study indicate that the Judicial Commission was established as a mechanism for checks and balances within the judicial system, as stipulated in Article 24B of the 1945 Constitution of the Republic of Indonesia and Law No. 18 of 2011. The Judicial Commission’s authority includes proposing the appointment of Supreme Court justices and overseeing the honor, dignity, and conduct of judges. From a maslahah perspective, these authorities aim to realize justice, maintain public trust in the judicial institution, and prevent the abuse of authority. Therefore, the existence of the Judicial Commission has a constitutional foundation as well as a value of public interest for society.